Scientific (Astro) Journalism Activities in Armenia - Darbinyan, L.; Mickaelian, A.; Farmanyan, S.
The significant media achievements of BAO are the result of dedicated efforts by its team of young and experienced scientists, whose passion for astronomy continues to inspire society. By combining transparent, creative, and strategic communication, BAO has built strong local and international visibility, serving as a bridge between past scientific milestones and future discoveries.
Keywords: Journalism